Representation of Wuling's Identity In Antaranews Media - Jakson Kumaat (Publikasi Indonesia, 2024)
This study aims to analyze the representation of Wuling's brand identity in the media of Antaranews, one of the leading news portals in Indonesia. Using a qualitative approach with a content analysis method, this study eval_uated 50 articles published in the period 2017 to 2023. The results of the analysis show that Wuling has succeeded in building a positive image through an emphasis on product quality, technological innovation, and after-sales service. However, there are challenges related to negative perceptions that are still attached to brands from China, especially regarding prices that are considered high. The study also found that the marketing communication strategies implemented by Wuling, including advertising campaigns and the use of social media, contributed to creating a positive buzz around their products. Thus, the study concludes that although Wuling has been successful in some aspects, market education and response to criticism are important steps to strengthen the brand's position in the Indonesian automotive market. These findings are expected to provide insights for the development of more effective communication strategies for Wuling and other brands in a competitive industry.